A review of neoplastic and non-neoplastic canine skin tumours in Trinidad from 2010-2015 - Suepaul, Rod; Rajh, Stacy; Frontera-Acevedo, Karelma; Pargass, Indira; Suepaul, Sharianne (Brazilian Journal of Veterinary Pathology, 2019)
This retrospective study was performed on samples submitted to the Pathology Unit of the School of Veterinary Medicine, Faculty of Medical Sciences, St. Augustine, Trinidad, during the period 2010 to 2015. A total of 471 non-inflammatory cutaneous masses were analyzed, of which 225 (47.8%) were malignant, 202 (42.9%) were benign and 44 (9.3%) were non-neoplastic. The most common malignant tumors were haemangiosarcoma, 50 (22.2%); mast cell tumour, 49 (21.8%); soft tissue sarcoma 35 (15.6%), lymphoma, 20 (8.9%) and melanoma 20 (8.9%). The most common benign tumors were haemangioma, 39 (19.3%); lipoma, 27 (13.4%), trichoblastoma, 26 (12.9%), histiocytoma 25 (12.4%), plasma cell tumor, 23 (11.4%) and papilloma 9 (4.5%). Common non-neoplastic skin lesions included collagen naevi, 26 (59.1%) and follicular cysts, 11 (25.0%). Mixed breed dogs 241 (51.2%), was most frequently represented with neoplasms followed by Rottweilers 50 (10.6%) and Pit bulls 48 (10.1%).